Temporal Trends in Sleep Pattern Among Chinese Adults Between 2010 and 2018 Findings from Five Consecutive Nationally Representative Surveys - De Moraes-Ferrari, G (Elsevier B.V., 2023)
Objectives: This study aimed to comprehensively analyze the time trends in average sleep duration and prevalence of short sleep, poor sleep quality, and high sleep debt among Chinese adults. Study design: This was a cross-sectional study. Methods: The study used nationally representative data from Chinese Family Panel Survey (CFPS) among adults aged ≥18 years. Linear regression and logistic regression were used to calculate P-values for trends across waves, and absolute difference in prevalences were calculated by linear regression. Poisson regression analysis was used to calculate the prevalence ratios of sleep-related problems. Results: In 2018, the estimated average sleep duration in adults was 7.6 h/d. A shorter sleep duration, higher proportion of short sleep, and poor sleep quality were observed in people aged ≥65 years, women, people with primary school education or below, and residents in Liaoning province. The average sleep duration slightly decreased from 8.2 h/d in 2010 to 7.6 h/d in 2016, and then remained stable from 2016 to 2018. The prevalence of short sleep duration has markedly increased from 11.8% in 2010 to 24.1% in 2016, and then there was a decline in prevalence from 2016 to 2018, although this decrease was not significant. The prevalence of high sleep debt among employed people increased from 6.2% in 2010 to 8.6% in 2018 (absolute difference, 2.4 p.p; P trend = 0.063). In addition, the prevalence of poor sleep quality increased from 15.6% in 2012 to 21.3% in 2018 (absolute difference of 5.7 p.p; P trend<0.001). For all the sleep-related variables, the degree of changes varied by sociodemographic subgroups. Conclusions: In this nationally representative survey of the Chinese population, the average sleep duration slightly decreased from 2010 to 2016, and then remained stable from 2016 to 2018. Poor sleep quality, and high sleep debt increased among most of the sociodemographic subgroups. Future studies are needed to understand the drivers of changes in sleep health among Chinese adults. © 2023 The Royal Society for Public Health